Sarcopenic obesity is attenuated by E-syt1 inhibition via improving skeletal muscle mitochondrial function - Chao Song; Wu Zheng; Guoming Liu; Yiyang Xu; Zhibo Deng; Yu Xiu; Rongsheng Zhang; Linhai Yang; Yifei Zhang; Guoyu Yu; Yibin Su; Jun Luo; et al. (Redox Biology)
In aging and metabolic disease, sarcopenic obesity (SO) correlates with intramuscular adipose tissue (IMAT). Using bioinformatics analysis, we found a potential target protein Extended Synaptotagmin 1 (E-syt1) in SO. To investigate the regulatory role of E-syt1 in muscle metabolism, we performed in vivo and in vitro experiments through E-syt1 loss- and gain-of-function on muscle physiology. When E-syt1 is overexpressed in vitro, myoblast proliferation, differentiation, mitochondrial respiration, biogenesis, and mitochondrial dynamics are impaired, which were alleviated by the silence of E-syt1. Furthermore, overexpression of E-syt1 inhibited mitophagic flux. Mechanistically, E-syt1 overexpression leads to mitochondrial calcium overload and mitochondrial ROS burst, inhibits the fusion of mitophagosomes with lysosomes, and impedes the acidification of lysosomes. Animal experiments demonstrated the inhibition of E-syt1 increased the capacity of endurance exercise, muscle mass, mitochondrial function, and oxidative capacity of the muscle fibers in OVX mice. These findings establish E-syt1 as a novel contributor to the pathogenesis of skeletal muscle metabolic disorders in SO. Consequently, targeting E-syt1-induced dysfunction may serve as a viable strategy for attenuating SO.